SHORT-TERM EFFICACY OF INTRAVITREAL BEVACIZUMAB IN TREATMENT NAIVE PATIENTS- REAL WORLD EVIDENCE IN PAKISTAN - Malik, Hajra Arshad; Sabih, Rayyan; Khalid, Maham; Khan, Hina; Asrar, Maha; Asrar, Aamir; Asif, Muhammad (Journal of Ayub Medical College Abbottabad, 2021)
Background: Anti-VEGF agents have been proven to be effective in treating macular oedema secondary to a multitude of pathological conditions. However, in large clinical trial settings, the results may be overstated. This study aimed to evaluate the short-term efficacy of intraocular Bevacizumab in consecutive patients with macular oedema being treated in a ’˜real-world’ setting in Pakistan. Methods: A prospective study was conducted at Amanat Eye Hospital, Rawalpindi from August 2018 to November 2019. Thirty-five eyes of 29 patients with macular oedema were treated with monthly intravitreal Bevacizumab injections for three consecutive months. Best-corrected visual acuity (BCVA), and OCT parameters including central retinal thickness (CRT) and macular volume were assessed prior to the injections and then 4 weeks post the final injection and compared. Results: BCVA improved from 1.00±0.44 at baseline to 0.83±0.48 four weeks after the third intravitreal injection. CRT decreased significantly from 492.77±192.31 at baseline to 362.91±126.11 (p<0.05), and macular volume decreased significantly from 11.61±2.39 at baseline to 9.87±1.68 (p<0.05) four weeks after the third intravitreal injection. No systemic or ocular complications were observed during the course of the study. Conclusion: Treatment with intravitreal Bevacizumab injections was found safe and resulted in clinically and statistically significant improvement in SD-OCT parameters and visual acuity in patients with macular oedema secondary to various retinal pathologies. However, the improvement in a real-world setting was sub-optimal in comparison to larger clinical trials for specific diseases in the developed world